Expression of SOX2 and OCT4 in odontogenic cysts and tumors - Phattarataratip, Ekarat (Head Face Med, 2021)
BACKGROUND: Aberrant expression of stem cell markers has been observed in several types of neoplasms. This trait attributes to the acquired stem-like property of tumor cells and can impact patient prognosis. The objective of this study was to comparatively analyze the expression and significance of SOX2 and OCT4 in various types of odontogenic cysts and tumors. METHODS: Fifty-five cases of odontogenic cysts and tumors, including 15 ameloblastomas (AM), 5 adenomatoid odontogenic tumors (AOT), 5 ameloblastic fibromas (AF), 5 calcifying odontogenic cysts (COC), 10 dentigerous cysts (DC) and 15 odontogenic keratocysts (OKC) were investigated for the expression of SOX2 and OCT4 immunohistochemically. RESULTS: Most OKCs (86.7 %) and all AFs expressed SOX2 in more than 50 % of epithelial cells. Its immunoreactivity was moderate-to-strong in all epithelial cell types in both lesions. In contrast, SOX2 expression was undetectable in AOTs and limited to the ameloblast-like cells in a minority of AM and COC cases. Most DCs showed positive staining in less than 25 % of cystic epithelium. Significantly greater SOX2 expression was noted in OKC compared with DC or AM, and in AF compared with COC or AOT. OCT4 rarely expressed in odontogenic lesions with the immunoreactivity being mild and present exclusively in OKCs. CONCLUSIONS: SOX2 is differentially expressed in odontogenic cysts and tumors. This could be related to their diverse cells of origin or stages of histogenesis. The overexpression of SOX2 and OCT4 in OKC indicates the acquired stem-like property. Future studies should investigate whether the overexpression of OCT4 and SOX2 contributes to the aggressive behaviors of the tumors.